(untitled) (World Bulletin of Social Sciences, 2023)
The Uzbek language, like other languages, has its own rules, in this respect, the tools that serve for expressive reading serve not only for expressive reading, but also for differentiating meaning. Words coming from other foreign languages help to enrich the Uzbek language. The correct pronunciation of the incoming words, it is precisely this language that encourages you to know the rules. Below we have familiarized ourselves with the accent rules of Uzbek and several foreign languages.